Early intervention program in youth-to-parent aggression: clinically relevant long-term changes - Ibabe, Izaskun (Journal of family violence, 2023)
Purpose: Practitioners in child and family services are able to identify cases of youth-to-parent aggression. The aim of this study was to evaluate long-term effects of the Early Intervention Program in Situations of Youth-to-Parent Aggression (EI-YPA), which was implemented in a Children and Family Services context on the outcome variables of adolescents and parents (individual behavior and health outcomes), indicating the strength of the evidence. Methods: The participants were members of 39 Spanish families with children between 12 and 17 years (N = 101; 40 adolescents and 61 parents) and a quasi-experimental design of repeated measures was applied. EI-YPA provides positive evidence and experiences based on the reports of children and parents. In order to analyze whether the improvements were clinically relevant, a reliable change index was used. Results: Significant improvements concerning aggressive behavior at home, clinical symptoms and family conflict were found. Effect sizes were large for aggressive behavior indicators (aggressive discipline d = 1.19; psychological YPA d = 0.93), and depressive symptomatology of adolescents (d = 0.80). Conclusion: The positive changes found indicate the long-term efficacy of the EI-YPA on behavioral variables and clinical symptoms of children and parents, as well as the family conflict perception. This study contributes to increasing the evidence quality of EI-YPA as a potential evidence-based program.